Europium in plagioclase-hosted melt inclusions reveals mantle melting modulates oxygen fugacity - Nicholas Dygert; Gokce K. Ustunisik; Roger L. Nielsen (Nature Communications, 2024)
Abstract To gain insights into the composition and heterogeneity of Earth’s interior, the partial pressure of oxygen (oxygen fugacity, or fO2) in igneous rocks is characterized. A surprising observation is that relative to reference buffers, fO2s of mantle melts (mid-ocean ridge basalts, or MORBs) and their presumed mantle sources (abyssal peridotites) differ. Globally, MORBs have near-uniform fO2s, whereas abyssal peridotites vary by about three orders of magnitude, suggesting these intimately related geologic reservoirs are out of equilibrium. Here, we characterize fO2s of mantle melting increments represented by plagioclase-hosted melt inclusions, which were entrapped as basaltic melts migrated from their sources toward the seafloor. At temperatures and fO2s constrained by rare earth element distributions, a range of fO2s consistent with the abyssal peridotites is recovered. The fO2s are correlated with geochemical proxies for mantle melting, suggesting partial melting of Earth’s mantle decreases its fO2, and that the uniformity of MORB fO2s is a consequence of the melting process and plate tectonic cycling.